Ocean Literacy across the Mediterranean Sea basin: Evaluating Middle School Students’ Knowledge, Attitudes, and Behaviour towards Ocean Sciences Issues - KOULOURI, PANAYOTA; MOGIAS, ATHANASIOS; MOKOS, MELITA; CHEIMONOPOULOU, MARIA; REALDON, GIULIA; BOUBONARI, THEODORA; PREVIATI, MONICA; TOJEIRO FORMOSO, ALBA; KIDEYS, AHMET ERKAN; HASSAAN, MOHAMED ALY; PATTI, PATRIZIA; KORFIATIS, KOSTAS; et al. (Mediterranean Marine Science, 2022)
The Mediterranean Sea is characterized by rich biodiversity, and its region hosts people living in several countries with a rich variety of cultures, but – at the same time – it is “under siege”, due to anthropogenic pressures. To address these pressures, many actions are needed aiming, among others, at establishing Ocean Literacy (OL) across the Mediterranean countries and preparing the future generation of Mediterranean Sea-literate citizens. Towards this aim, the present cross-national study investigated OL issues in relation to content knowledge, possible common misconceptions, attitudes, and the self-reported behavior of 2,533 middle school students from eight Mediterranean countries (Croatia, Cyprus, Egypt, Greece, Italy, Malta, Spain, and Turkey), as well as certain background elements (e.g., gender, grade level, environmental education experience, sources of relevant information). The results of this study revealed that middle school students of all studied countries possess a moderate level of ocean sciences content knowledge, while they showed satisfactory pro-environmental attitudes and behavior. These findings along with further research are expected to function as a baseline for the design, implementation, and launch of specifically targeted programs, educational activities, teaching resources, curricula, and school textbooks, which will be achieved through close collaboration between schools, universities, research institutes, and Ministries of Education, thus contributing to the future protection and sustainable development of the Mediterranean Sea region.